Mediação do fonoaudiólogo no processo de capacitação do professor do aluno surdo - Tenor, Ana Cláudia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The inclusion of deaf students in regular schools has generated discussions and polemics among researchers, professionals and families seeking for a better quality of education for these students. In this context, the education and training of teachers are considered targets to be met. The aim of this study was to systematize actions to train teachers of deaf students by mediation of speech therapists. A father, a mother and two teachers of deaf students from a city inland in São Paulo State have participated in this study. In the first part parents and teachers of these students were interviewed, the adapted Protocol Paula (2007) was applied to assess the communication skills of these student within school environment and observations have been conducted in the classroom. Protocol data and observations were incorporated into the transcripts of the interviews, constituting a single text according to assumptions of data triangulation Triviños (1992). The content analysis was performed according to Bardin (2004), which consisted of thematic units classification. From the themes identified in Part 1, a training program has been developed to involve the family and the teachers. The methodology initially proposed was the focal group, adapting the model used by Ferreira (2006). Due to the lack of adhesion of families the methodological procedure has been modified to training courses in a group, which occurred through discussions with teachers. During the second stage teachers took part in group training, filming, observations and mediations of the researcher also occurred in the classroom. The meetings were recorded and the material was transcribed and then organized into notebooks content. The data from these notebooks, records of observations and recordings were triangulated according to Triviños (1992) generating themes and subthemes analysis. In the third part, opinions about the speech therapist participation in the training program...

A inclusão de alunos surdos na escola regular tem gerado discussões e polêmicas entre pesquisadores, profissionais e familiares que buscam uma melhor qualidade de ensino a esses alunos. Nesse contexto, a formação e capacitação dos professores são consideradas metas a serem atingidas. O objetivo desse estudo foi sistematizar ações para a capacitação do professor do aluno surdo por meio da mediação do fonoaudiólogo. Participaram um pai, uma mãe e duas professoras de alunos surdos incluídos de um município do interior de São Paulo. Na primeira etapa foram entrevistados os pais e professores desses alunos, aplicado o Protocolo adaptado de Paula (2007) para avaliação de habilidades comunicativas do aluno em ambiente escolar e realizadas observações em sala de aula. Os dados do protocolo e das observações foram incorporados as transcrições das entrevistas, constituindo um texto único conforme os pressupostos de triangulação de dados de Triviños (1992). Foi realizada análise de conteúdo segundo Bardin (2004), que consistiu em classificação de unidades temáticas. A partir das temáticas identificadas na Etapa 1 foi elaborado um programa de capacitação com a intenção de envolver a família e professores. A metodologia inicialmente proposta foi o grupo focal, adequando o modelo usado por Ferreira (2006). Em virtude da falta de adesão das famílias foi modificado o procedimento metodológico para grupo de capacitação, que ocorreu por meio de discussões com os professores. Durante a segunda etapa houve a participação dos professores no grupo de capacitação, ocorreram também filmagens, observações e mediações da pesquisadora em sala de aula. Os encontros foram gravados, o material foi transcrito e organizado em cadernos de conteúdo. Os dados provenientes desses cadernos, os registros das observações e filmagens foram triangulados, segundo Triviños (1992), gerando temas e subtemas de análise. Na...
Keywords: Educação inclusiva; Surdez; Professores - Formação; Inclusive education